Myeloid cell‐specific mutation of Spi1 selectively reduces M2‐biased macrophage numbers in skeletal muscle, reduces age‐related muscle fibrosis and prevents sarcopenia. Issue 10 (13th September 2022) - Wang, Ying; Welc, Steven S.; Wehling‐Henricks, Michelle; Kong, Ying; Thomas, Connor; Montecino‐Rodriguez, Enca; Dorshkind, Kenneth; Tidball, James G.
Abstract: Intramuscular macrophages play key regulatory roles in determining the response of skeletal muscle to injury and disease. Recent investigations showed that the numbers and phenotype of intramuscular macrophages change during aging, suggesting that those changes could influence the aging process. We tested that hypothesis by generating a mouse model that harbors a myeloid cell‐specific mutation of Spi1, which is a transcription factor that is essential for myeloid cell development. The mutation reduced the numbers of macrophages biased to the CD163+/CD206+ M2 phenotype in muscles of aging mice without affecting the numbers of CD68‐expressing macrophages and reduced the expression of transcripts associated with the M2‐biased phenotype. The mutation did not affect the colony‐forming ability or the frequency of specific subpopulations of bone marrow hematopoietic cells and did not affect myeloid/lymphoid cell ratios in peripheral blood leukocyte populations. Cellularity of most myeloid lineage cells was not influenced by the mutation. The Spi1 mutation in bone marrow‐derived macrophages in vitro also did not affect expression of transcripts that indicate the M2‐biased phenotype. Thus, myeloid cell‐targeted mutation of Spi1 influences macrophage phenotype in muscle but did not affect earlier stages of differentiation of cells in the macrophage lineage. The mutation reduced age‐related muscle fibrosis, which is consistent with the reduction of M2‐biased macrophages, and reduced expression of the pro‐fibrotic enzyme arginase. Most importantly, the mutation prevented sarcopenia. Together, our observations indicate that intramuscular, M2‐biased macrophages play significant roles in promoting detrimental, age‐related changes in muscle. Abstract : Muscle aging leads to sarcopenia, which is characterized by reductions in muscle mass and muscle fiber size and is also associated with increases in muscle fibrosis. In our investigation, we show that the targeted mutation of the transcription factor Spi1 in myeloid cells, causes a selective reduction in the activation of intramuscular macrophages to an M2‐biased phenotype and that leads to reductions in sarcopenia and fibrosis during muscle aging. These findings show an important role for M2‐biased macrophages in age‐related changes in skeletal muscle.